Computational and traveling wave analysis of Tzitzeica and Dodd-Bullough-Mikhailov equations: An exact and analytical study - Durur, Hulya; Yokus, Asif; Abro, Kashif Ali (Walter de Gruyter Gmbh, 2021)
Computational and travelling wave solutions provide significant improvements in accuracy and characterize novelty of imposed techniques. In this context, computational and travelling wave solutions have been traced out for Tzitzeica and Dodd-Bullough-Mikhailov equations by means of (1/G') -expansion method. The different types of solutions have constructed for Tzitzeica and DoddBullough-Mikhailov equations in hyperbolic form. Moreover, solution function of Tzitzeica and Dodd-BulloughMikhailov equations has been derived in the format of logarithmic nature. Since both equations contain exponential terms so the solutions produced are expected to be in logarithmic form. Traveling wave solutions are presented in different formats from the solutions introduced in the literature. The reliability, effectiveness and applicability of the (1/G') -expansion method produced hyperbolic type solutions. For the sake of physical significance, contour graphs, two dimensional and three dimensional graphs have been depicted for stationary wave. Such graphical illustration has been contrasted for stationary wave verses traveling wave solutions. Our graphical comparative analysis suggests that imposed method is reliable and powerful method for obtaining exact solutions of nonlinear evolution equations.
Keywords: Tzitzeica equation; (1/G ') -expansion method; Dodd-Bullough-Mikhailov equation; traveling wave solutions; exact solutions